2020
DOI: 10.3847/2041-8213/ab79a4
|View full text |Cite
|
Sign up to set email alerts
|

Spitzer Observations of the Predicted Eddington Flare from Blazar OJ 287

Abstract: Binary black hole (BH) central engine description for the unique blazar OJ287 predicted that the next secondary BH impact-induced bremsstrahlung flare should peak on 2019 July 31. This prediction was based on detailed general relativistic modeling of the secondary BH trajectory around the primary BH and its accretion disk. The expected flare was termed the Eddington flare to commemorate the centennial celebrations of now-famous solar eclipse observations to test general relativity by Sir Arthur Eddington. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 27 publications
5
55
0
1
Order By: Relevance
“…This article emphasizes the importance of continuing monitoring of OJ 287 at all wavelengths of the electromagnetic spectrum as well as in gravitational waves. Even though the binary orbit has now been solved [33] and confirmed [34], there are many aspects of the system which still need verification and from which we can learn interesting astrophysics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article emphasizes the importance of continuing monitoring of OJ 287 at all wavelengths of the electromagnetic spectrum as well as in gravitational waves. Even though the binary orbit has now been solved [33] and confirmed [34], there are many aspects of the system which still need verification and from which we can learn interesting astrophysics.…”
Section: Discussionmentioning
confidence: 99%
“…The 2005 flare came a week ahead of the orbital schedule calculated by Sundelius et al [44] and corrected for the astrophysical time shift between the disk impact and the flare by LV96 [47,48]. The latest prediction of the 2019 Eddington flare was successfully observed with the Spitzer space telescope [34] which showed that the orbital times are now known with the accuracy of ±4 h.…”
Section: Oj 287 and Its Bh Binary Central Engine Descriptionmentioning
confidence: 99%
“…It has been demonstrated in the past that it is possible to measure spininduced multipole moments for intermediate mass-ratio [173,174] and extreme mass-ratio inspirals [175,176]. This parameter can also be constrained through electromagnetic observations of active galactic nuclei (see [177] for a recent measurement) and supermassive BHs [178].…”
Section: B Spin-induced Quadrupole Momentmentioning
confidence: 99%
“…The 2015-2016 The shaded regions mark the spectrally distinct high MW activity periods while the non-shaded parts trace the spectral transition and its evolution. The blue vertical dashed lines are the claimed time of the impact flares (Valtonen et al, 2016;Laine et al, 2020) while the black vertical dashed lines represent long-exposure observations by the AstroSat (Singh et al, 2021;Kushwaha et al, 2021).…”
Section: Oj 287mentioning
confidence: 99%
“…The observational features that have made OJ 287 unique and untypical blazar are the claim of a persistent quasi-periodic ∼ 12-yr signal in optical bands (Sillanpaa et al, 1988;Dey et al, 2018;Laine et al, 2020), a yearly quasi-periodic variations in the location of quasistationary knots seen in radio images (Britzen et al, 2018) as well as claims of ∼ 22-yr (Britzen et al, 2018) and ∼ 30-yr periods (Cohen, 2017), and many transient spectral features like a sharp break in the NIR-optical spectrum (Kushwaha et al, 2018a, an extremely soft X-ray spectra dominated spectral state (Komossa et al, 2017(Komossa et al, , 2020 with a broadband spectrum similar to presence of an additional HBL-like emission component (Kushwaha et al, 2018b and peculiar timing trends untypical of blazars (Kushwaha et al, 2018b;Komossa et al, 2020;Huang et al, 2021), a Seyfert-like soft X-ray excess state , an iron line absorption feature (Komossa et al, 2020), an spectral cutoff in the high-energy end of the optical synchrotron spectrum (Singh et al, 2021;Kushwaha et al, 2021), etc. Regarding the ∼ 12-yr QPOOs, it should be noted that studies employing diverse and state-of-art timing methodologies (Peñil et al, 2020;Goyal et al, 2018) dispute the ∼ 12-yr recurrent optical outbursts.…”
Section: Oj 287mentioning
confidence: 99%